Legal Synchronization between Government Policy and Sharia Concepts on Lockdown Discourse during the Covid 19 Pandemic - Nurdin, Zefrizal (al-'adalah, 2021)
This article aims to analyze government policies related to Large-Scale Social Restriction Policy (PSBB), known as lockdown,  through the concept of Islamic law to find legal synchronization between the policy and the concept of sharia. The problem that will be answered in this study is how Islamic law regulates PSBB when an infectious disease occurs, and whether the PSBB policy has been intertwined with the provisions of the Shari'ah. This research is a normative-juridical that focuses on the problem of synchronization between the two legal systems; sharia and positive law. The results show that Shari'a provisions explicitly require that a lockdown be imposed for anyone and any interest (including collective worship activities) in an infectious area, except for medical personnel carrying out the mandate to provide health services to the community. Prohibition of going out or entering the disaster area can lead to the legal status of haram (strongly prohibited) or makruh (Lessly prohibited) depending on the level of emergency it causes based on information from medical experts. Thus there is a legal synchronization between the provisions of the Shari'a and government policies related to the lockdown, the policies that must be adhered to by citizens for the safety of the individuals and the people as well.Keywords: Covid-19, PSBB, synchronization of law.